2001
DOI: 10.1515/znb-2001-0210
|View full text |Cite
|
Sign up to set email alerts
|

Synthese und Charakterisierung von cis- und trans-Dicyclohexyl-3,3′,4,4′- tetracarbonsäuren und ihren Dianhydriden / Syntheses and Characterization of cis- and trans-Dicyclohexyl-3,3′,4,4′- tetracarboxylic Acids and their Dianhydrides

Abstract: Acids, Dianhydrides, Isomerization cis-and rra«s-Dicyclohexyl-3,3',4,4'-tetracarboxylic acid and their dianhydrides were pre pared from tetramethyl dicyclohexyl-3,3',4,4'-tetra-carboxylates by hydrolysis and subse quent dehydration. The trans dianhydride 2b was found to be sensitive to temperature. Ho wever, once the imide ring is formed in the reaction with an amine, the model compound is thermostable. The products were characterized by ]H and 13C NMR, and also by two-dimen sional COSY spectroscopy. In the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“…The measured T g for the H-BPDA/4,4′-ODA (246 °C by DMA at 0.1 Hz, Table 8 ) was also approximate to that for the cis -DCDA/4,4′-ODA film reported in the literature (259 °C by DSC [ 33 ] and 256 °C by DMA at 1 Hz [ 42 ]). These results do not conflict with the aforementioned prediction, based on the 1 H-NMR spectral similarity, that H-BPDA used in this study has essentially the same steric structure as cis -DCDA [ 33 , 64 ].…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…The measured T g for the H-BPDA/4,4′-ODA (246 °C by DMA at 0.1 Hz, Table 8 ) was also approximate to that for the cis -DCDA/4,4′-ODA film reported in the literature (259 °C by DSC [ 33 ] and 256 °C by DMA at 1 Hz [ 42 ]). These results do not conflict with the aforementioned prediction, based on the 1 H-NMR spectral similarity, that H-BPDA used in this study has essentially the same steric structure as cis -DCDA [ 33 , 64 ].…”
Section: Resultssupporting
confidence: 74%
“…The crystallization of H-BPDA-based model compounds was unsuccessful. Hence, the steric structure of H-BPDA used in this study was predicted by comparing its spectral data that we measured with those reported in the literature [ 33 , 42 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations